2018
DOI: 10.3390/en11123293
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Second-Stage of Rotor with Single Abnormal Blade Angle on Rotating Stall of a Two-Stage Variable Pitch Axial Fan

Abstract: It is of great value to study the impact of abnormal blade installation angle on the inducement mechanism of rotating stall to achieve the active control of rotating stall in an axial fan. Based on throttle value function and SST k-ω turbulence model, numerical simulations of the unsteady flow process in stall condition of an axial flow fan with adjustable vanes were carried out, and the influence mechanism of abnormal stagger angle of a single blade in the second stage rotor on induced position and type of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Furthermore, with the transformation of the vortex breakdown form, the characteristic frequency and amplitude of the flow oscillation substantially changed. Tip leakage flow through the radial clearance between the blade tip and the casing has gained extensive attention by researchers in the turbomachinery field due to the fact that it contributes a significant portion of the overall loss [1] and has significant effects on the performance and stability of compressors [2][3]. The tip clearance flow field is characterized by a streamwise slender vortex, i.e.…”
mentioning
confidence: 99%
“…Furthermore, with the transformation of the vortex breakdown form, the characteristic frequency and amplitude of the flow oscillation substantially changed. Tip leakage flow through the radial clearance between the blade tip and the casing has gained extensive attention by researchers in the turbomachinery field due to the fact that it contributes a significant portion of the overall loss [1] and has significant effects on the performance and stability of compressors [2][3]. The tip clearance flow field is characterized by a streamwise slender vortex, i.e.…”
mentioning
confidence: 99%
“…However, changes in these parameters are finally reflected with changes in integral parameters. Therefore, the verification method using integral parameters is widely applied in many researches [21,[24][25][26][27]. To verify the mesh independence, fans with mesh numbers of 3.82, 4.26, 4.65, 5.33 and 5.56 million are simulated in this study, as shown in Table 3.…”
Section: Meshingmentioning
confidence: 99%
“…Furthermore, the stall margin expanded by approximately 5% and the noise reduced by about 3 dB. With respect to the influence of varying the blade pitch angle, some reports have described the effect of an abnormal blade angle on the aerodynamic and acoustic performance of an axial fan [20,21]. Gou et al [22] studied the effect of the blade pitch angle on the pressure loss of a parallel fan station.…”
Section: Introductionmentioning
confidence: 99%
“…Trebinjac Isabelle [2] conducted numerical simulations and experiments on a transonic centrifugal compressor and explored the unsteady physical mechanisms that affect compressor performance, such as impellers and diffusers coupling loss and the periodic changes of shock waves, and proposed an analytical model for loss correction in steady-state calculation. The instability of the rotating stall and surge under low flow conditions also greatly affects the performance of compressor [3][4][5]. Taher Halawa [6] carried out numerical simulations studying the rotating stall and surge conditions of centrifugal compressors with and without vanes respectively, and compared the flow characteristics of the two compressors.…”
Section: Introductionmentioning
confidence: 99%